Abundance and physical factors affecting the appearance of selected terrestrial birds in Khao Yai National Park using camera trapping - Pemika Kanka; Ronglarp Sukmasuang; Prateep Duengkae; Kittiwara Siripattaranukul (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Kanka P, Sukmasuang R, Duengkae P, Siripattaranugul K. 2023. Abundance and physical factors affecting the appearance of selected terrestrial birds in Khao Yai National Park using camera trapping. Biodiversitas 24: 222 232. This study used results from camera traps set for Dhole (Cuon alpinus) and their prey during 2017-2020 in Khao Yai National Park to assess the species richness of ground-dwelling birds and identify abundance and also temporal appearance of the species in the area. We selected only the Pheasant species that typically forage on the ground to investigate the physical factors affecting the appearance in Khao Yai National Park. Based on camera trapping data with a total of 4139 trap days, 115 camera locations showed 36 species of birds belonging to 21 families, and 13 orders of ground-dwelling bird species were recorded. Siamese Fireback (Lophura diardi), Red Junglefowl (Gallus gallus), and Silver Pheasant (Lophura nycthemera) were detected with an abundance index of 10.65%, 7.27%, and 1.84%, respectively. The ground-dwelling bird abundance index from the camera traps accounted for 26.85% of the total fauna. Although the Phasianidae were found to be diurnal species, this study also shows a statistically significant difference in the average time between Red Junglefowl and Siamese Fireback. Meanwhile, there was no statistically significant difference between Red Junglefowl and Silver Pheasant during their active time. The water sources showed a significant effect on the presence of the Siamese Fireback in data analysis; however, no physical environmental factors significantly affected the distribution of Red Junglefowl and Silver Pheasant. This study found that surrounding creeks and streams significantly impacted the appearance of the Siamese Fireback. As a result, area management needs to prevent and reduce disturbances along a creek in order to effectively manage the habitat of the Siamese Fireback and other wildlife.